2022
DOI: 10.1097/md.0000000000031692
|View full text |Cite
|
Sign up to set email alerts
|

A pooled analysis of the association between sarcopenia and osteoporosis

Abstract: Background: Sarcopenia is a progressive generalized skeletal muscle disorder that causes the accelerated loss of muscle mass and function. Osteoporosis is a systemic condition of the skeleton that results in low bone mass and quality. Several studies have suggested that osteoporosis and sarcopenia are interrelated; however, a few studies indicate the lack of a significant association between sarcopenia and osteoporosis. We aimed to evaluate the association between sarcopenia and osteoporosis via a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
(145 reference statements)
0
11
0
Order By: Relevance
“…On the other hand, the diagnosis of sarcopenia may vary due to the use of different cutoff values for grip strength and walking speed, potentially leading to differences in the prevalence of sarcopenia. To our knowledge, findings from various studies ( 18 , 53 ), including a meta-analysis ( 54 ), suggest that sarcopenia represents a risk factor for osteoporosis. Therefore, we believe that there is a bidirectional relationship between sarcopenia and osteoporosis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, the diagnosis of sarcopenia may vary due to the use of different cutoff values for grip strength and walking speed, potentially leading to differences in the prevalence of sarcopenia. To our knowledge, findings from various studies ( 18 , 53 ), including a meta-analysis ( 54 ), suggest that sarcopenia represents a risk factor for osteoporosis. Therefore, we believe that there is a bidirectional relationship between sarcopenia and osteoporosis.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have identified AGEs and osteoporosis as independent risk factors for sarcopenia and a bidirectional relationship between osteoporosis and sarcopenia ( 11 , 18 , 19 , 53 , 54 ). However, the specific mechanism by which AGEs affect sarcopenia through osteoporosis and how sarcopenia affects osteoporosis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic analysis of 38 studies including 224,321 participants suggested that sarcopenia increased the risk of osteoporosis by 3.06 times. In addition, this systematic analysis also included 7 trials involving 171,514 participants revealed that each standard deviation (SD) increase in relative appendicular skeletal muscle mass (RASM) was associated with a significant 35% reduction in osteoporosis risk ( 50 ). Ahn et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a condition of the muscles characterized by a loss of muscle mass and strength ( Vogele et al, 2023 ). This condition is linked to osteoporosis for multiple reasons, including the same risk factors, similar etiological pathways, endocrine basis, and the phenomenon of bidirectional bone-muscle crosstalk ( Yu et al, 2022 ; He et al, 2020 ). Sarcopenia is also associated with frailty syndrome.…”
Section: Discussionmentioning
confidence: 99%